(untitled) (International Journal of Physiotherapy, 2023)
Background: To establish an objective evaluation of basic physiotherapy technique, we recorded a mechanical aspect during a lateral weight-shifting (WS) using gravicorder. Methods: Subjects were 18 physiotherapists divided into three groups based on experience year. Our originally developed software converted center of gravity data during WS to 3-dimensional mechanical value. Results: All direction data showed significantly lower in the long experience year group (p<0.05). The coefficient of variation was high vertical for all three groups. Conclusion: In the group with more years of experience, it was confirmed that it was compactly implemented. In the vertical direction, it is thought to be implemented by empirical rules because there is no constant normal pattern or common recognition among physiotherapists.